Bicentennial, violence and community psychology - Bautista, Nelly Patricia (Pensando Psicología, 2010)
This essay demands to understand how Conquest, Colony and Independence history of our country has a common issue in violence which currently has effects on reality by means of mental representations, defensive strategies and actions typical of a subdued population. Historical memory provides meaning to every expression from words, feelings and concepts that constitute community’s mental framework in a socio-historical juncture. Thus, community psychology should recognize the connector between roots of our history and everyday life in order to create strategies, which allow to overcome the psychosocial consequences that a history marked by terror and social inequality has left, seeking to reconcile traditionwith novelty to confront the trend to assume a defensive attitude towards human and institutional relations.Violence as a psychosocial construct is objectified by the way a certain individual or group defines himself/itself as part of their social interaction’s context. Hence, it’s crucial for Colombian psychologist to incorporate valid explanations about social facts in accordance with history which we haven’t assimilated completely nor overcome.
Keywords: bicentennial; identity; independence; community; psychology; violence